Stabilizing of Inverted Pendulum System Using Robust Sliding Mode Control - Magdi S. Mahmoud; Radhwan A. A. Saleh; Alfian Ma’arif (Association for Scientific Computing Electronics and Engineering (ASCEE), 2022)
The Inverted Pendulum is a highly nonlinear, unstable, and fast dynamic system. These characteristics make it a popular benchmark for building and testing novel controllers. Therefore, in this study, a sliding mode controller is proposed and tested on the inverted pendulum system. According to the results of the simulation experiments with a sine signal as a reference, the proposed controller can stabilize the system well and has so fast response. Moreover, we have tuned the parameters of the proposed sliding mode controller in order to eliminate the chattering effect, the overshoot, and the steadystate error.